4-PBA inhibits LPS-induced inflammation through regulating ER stress and autophagy in acute lung injury models - Zeng, Meichun; Sang, Wenhua; Chen, Sha; Chen, Ran; Zhang, Hailin; Xue, Feng; Li, Zhengmao; Liu, Yu; Gong, Yongsheng; Zhang, Hongyu; Kong, Xiaoxia (Toxicology letters, 2017)
•4-PBA protects LPS-induced acute lung injury and inflammation in mouse model.•4-PBA decreases the levels of ER stress and autophagy induced by LPS in vivo and in vitro.•Inhibition of autophagy by 3-MA aggravates cell injury induced by LPS, ER stress-associated autophagy may play a protective effect in LPS-induced lung injury. Acute lung injury (ALI) is a common clinical disorder that causes substantial health problems worldwide. An excessive inflammatory response is the central feature of ALI, but the mechanism is still unclear, especially the role of endoplasmic-reticulum (ER) stress and autophagy. To identify the cellular mechanism of lung inflammation during lipopolysaccharide (LPS)-induced mouse model of ALI, we investigated the influence of classic ER stress inhibitor 4-phenyl butyric acid (4-PBA) on ER stress and autophagy, which partially affect the activation of inflammation, both in LPS-induced ALI mouse model and human alveolar epithelial cell model. We demonstrated that 4-PBA, which further prevented the activation of the NF-κB pathway, decreased the release of the pro-inflammatory mediators IL-1β, TNF-α and IL-6, significantly inhibited LPS-activated ER stress. Moreover, it was found that autophagy was also decreased by the treatment of 4-PBA, which may play a protective role in ALI models through the classical AKT/mTOR signaling pathway. Inhibition of autophagy by 3-MA exacerbates cytotoxicity induced by LPS in A549 alveolar epithelial cells. Taken together, our study indicated that ER stress is a key promoter in the induction of inflammation by LPS, the protective effect of 4-PBA is related to the inhibition of ER stress and autophagy in LPS-induced ALI models. Furthermore, the role of autophagy that contributes to cell survival may depend on the activation of ER stress.